1995
DOI: 10.1007/bf01874874
|View full text |Cite
|
Sign up to set email alerts
|

Development of apothecia ofTapesia yallundae in contrasting populations selected by fungicides

Abstract: Apothecia of the eyespot fungus, Tapesia yallundae, were found on 0--18% of straws in plots of wheat stubble in February-March 1994. The fungicides carbendazim, prochloraz or carbendazim plus prochloraz had been applied repeatedly to the same plots in each of the previous 9 years in which successive wheat crops had been grown. The factors most strongly correlated with the incidence of apothecia were the incidence and severity of eyespot in the preceding wheat crop and the frequency of carbendazim-resistant W-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Slight to moderate eyespot infection, thought to arise from inoculation with T. acuformis , was observed on ≈ 25% of culms (both wheat and barley) in all the field plots inoculated in spring 1995 (infection levels assessed as described by Bateman et al ., 1995). However, apothecia were not detected on any of the stubble collected in spring 1996.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Slight to moderate eyespot infection, thought to arise from inoculation with T. acuformis , was observed on ≈ 25% of culms (both wheat and barley) in all the field plots inoculated in spring 1995 (infection levels assessed as described by Bateman et al ., 1995). However, apothecia were not detected on any of the stubble collected in spring 1996.…”
Section: Resultsmentioning
confidence: 93%
“…These included infecting crops with isolates known to be of complementary mating type and able to produce apothecia in vitro (Dyer et al ., 1996; Moreau & Maraite, 1996), with increased inoculum used in the second set of field experiments to ensure thorough disease progress. It has previously been shown that the abundance of apothecia of T. yallundae on stubble is significantly associated with the incidence of eyespot disease in the preceding crop (Bateman et al ., 1995). One previous attempt to induce the sexual cycle of T. acuformis in vivo also failed, but this may have been due to a lack of isolates of complementary mating type (Dyer et al ., 1994a).…”
Section: Discussionmentioning
confidence: 99%
“…In one study on PDA, colonies of T. acuformis produced more conidia than colonies of T. yallundae , but these differences were not consistent in controlled‐environment experiments or in field experiments in different seasons (Harvey, 1992). Additionally, it is not clear whether airborne ascospores produced by T. yallundae (observed on this experimental site when it was in set‐aside in 1993/94 by Bateman et al. , 1995) and T. acuformis play a role in the initiation of new epidemics in autumn, nor whether the numbers of such ascospores produced differ between the two species (Bateman & Jenkyn, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal differences may relate to differences in concentrations of inoculum, as increased inoculum concentration increased rates of leaf sheath infection/penetration and eyespot incidence. However, the roles of ascospores and conidia of the two species as the primary inoculum initiating epidemics are not clear (Bateman et al ., 1995). Seasonal differences may also relate to differences in the timing of infection by pathogen spores, which affected the severity of eyespot in container experiments.…”
Section: Discussionmentioning
confidence: 99%
“…If factors affecting the progress of OY and OA are better understood, it should be easier to relate early incidence of eyespot to its final incidence. Fungicide‐resistant strains of both eyespot species occur in the UK, and fungicide use has affected the population dynamics of the two species (Bateman et al ., 1995). Recent work suggests that niche differences exist between OY and OA, and that differential fungicide selection has changed eyespot populations in the UK (Bateman et al ., 1990b; Fitt et al ., 1990; Bateman, 2002; Bierman et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%